Supersaturable self-microemulsifying drug delivery system enhances dissolution and bioavailability of telmisartan. (2nd January 2021) - Park, Sun Young; Jin, Chang Hwa; Goo, Yoon Tae; Chae, Bo Ram; Yoon, Ho Yub; Kim, Chang Hyun; Song, Seh Hyon; Han, Sang Beom; Choi, Young Wook
Abstract: To enhance the dissolution and oral bioavailability of telmisartan (TMS), a poorly water-soluble anti-hypertensive drug, a supersaturable self-microemulsifying drug delivery system (SuSMEDDS) was developed. Amorphous alkalinized TMS (AAT) was formulated into a SMEDDS, composed of Capmul® MCM (oil), Cremophor ® RH40 (surfactant), and tetraglycol (co-surfactant). Although the SMEDDS was rapidly dissolved (>80% within 5 min) in a limited condition (500 mL, pH 6.8), drug precipitation was observed over time, resulting in a decrease in dissolution levels. The precipitation was due to drug recrystallization, as determined by differential scanning calorimetry and powder X-ray diffraction analyses. Several polymers, including Soluplus ® (SOL), were screened as precipitation inhibitors; ultimately, SuSMEDDS-SOL was prepared by admixing SOL and the SMEDDS at a 5:100 (w/w) ratio. SuSMEDDS-SOL was superior in terms of dissolution efficiency (>90% over 2 h) and dissolution-retaining time (no precipitation over 2 h). An in vivo pharmacokinetic study in rats revealed that the oral bioavailability of SuSMEDDS-SOL was 4.8-, 1.3-, and 1.2-fold greater than those of the TMS suspension, AAT solution, and SMEDDS, respectively. Therefore, SuSMEDDS-SOL is a promising candidate to enhance the dissolution and oral bioavailability of TMS.